Cyclophilin A secreted from fibroblast-like synoviocytes is involved in the induction of CD147 expression in macrophages of mice with collagen-induced arthritis - Nishioku Tsuyoshi; Dohgu Shinya; Koga Mitsuhisa; Machida Takashi; Watanabe Takuya; Miura Teppei; Tsumagari Kousuke; Terasawa Mariko; Yamauchi Atsushi; Kataoka Yasufumi (BMC, 2012)
Abstract Background Cyclophilin A (CypA), a member of the immunophilin family, is a ubiquitously distributed intracellular protein. Recent studies have shown that CypA is secreted by cells in response to inflammatory stimuli. Elevated levels of extracellular CypA and its receptor, CD147 have been detected in the synovium of patients with RA. However, the precise process of interaction between CypA and CD147 in the development of RA remains unclear. This study aimed to investigate CypA secretion from fibroblast-like synoviocytes (FLS) isolated from mice with collagen-induced arthritis (CIA) and CypA-induced CD147 expression in mouse macrophages. Findings CIA was induced by immunization with type II collagen in mice. The expression and localization of CypA and CD147 was investigated by immunoblotting and immunostaining. Both CypA and CD147 were highly expressed in the joints of CIA mice. CD147 was expressed in the infiltrated macrophages in the synovium of CIA mice. In vitro, spontaneous CypA secretion from FLS was detected and this secretion was increased by stimulation with lipopolysaccharide. CypA markedly increased CD147 levels in macrophages. Conclusions These findings suggest that an interaction in the synovial joints between extracellular CypA and CD147 expressed by macrophages may be involved in the mechanisms underlying the development of arthritis.